Overview of anticonvulsant therapy in full-term and premature neonates - M. A. Ivzhits; S. K. Zyryanov; G. V. Rodoman; I. B. Bondareva; S. V. Dumova; O. A. Babak; M. S. Chenkurov; G. A. Putsman (Русский журнал детской неврологии)
Convulsions in full-term and especially in premature newborns are observable pathologies. Selection of anticonvulsant therapy is very difficult: newborns have particular pharmacokinetics of drugs, insufficient data on doses and therapeutic concentrations of anticonvulsants in the blood (premature infants mainly). This article is an overview, with an emphasis on the features of dosing and pharmacokinetics of anticonvulsants in term and preterm infants.